ASSESMENT OF ANTIOXIDANT AND CYTOTOXIC ACTIVIY OF ESSENTIAL OIL EXTRACTED FROM LAVANDULA ANGUSTIFOLIA CALLUS LEAVES - Hamad, S. F.; Salman, Z. O.; Alwash, B. M. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to estimate the effect of essential oil extracted from callus of Lavandula angustifolia leaves as antioxidant and cytotoxic activity (in vitro). Different concentrations of essentail oil were selected, including 20, 40, 60, 80 and 100 µg/ml in determining antioxidant activity by using Free radical 1,1 Dyphenyl-2-picrylhydrazyl radical (DPPH). The results showed the efficacy of essentail oil as an antioxidant and the highest effect at 100 µg/ml reaching 97% and 87% at 80 µg/ml respectively. Different concentrations of essential oil ( 12.5, 25, 50,75 and 100) µg/ml were select to determine the effect of oil on human cervical cancer (HeLa) cancer cell line and a breast epithelial cell line (HBL) normal cell line after 72 hours from exposure time, and then antiproliferative activity of this oil was studied using MTT assay. The results showed the oil of L. angustifolia callus have high antioxidant influence (97%) in 100 µg/ml concentration followed by (87%) in concentration 80 µg/ml. The inhibition effect of extract on cell proliferation in HeLa cell line at highest concentration which reached 77%. The study confirmed the possibility of using essential oil from L. angustifolia callus could be used for medical application and treatment various types of cancer disease.